Analysis of the implementation path of medical-prevention integration in public hospitals in China from an integrated care perspective - Linxiu REN; Tianyi ZHANG; Chunxue YOU; Siyu TAO (Zhongguo gonggong weisheng)
Public hospitals constitute the main body of China′s healthcare system and are a crucial force in comprehensively promoting the construction of a "Healthy China". Guiding the medical-prevention integration in public hospitals with the concept of integrated care is key to fully implementing the “Healthy China” strategy, a means of shifting disease control and management upstream, and the optimal strategy for achieving whole-life-cycle health management. This article reviews the background and necessity of implementing medical-prevention integration in public hospitals, summarizes the current status and problems of such integration in China, and, guided by the concept of integrated care, explores implementation path for medical-prevention integration in Chinese public hospitals from five perspectives: functional integration, financing integration, personnel integration, model integration, and information integration. The aim is to promote the development of medical-prevention integration in public hospitals in China.